Effect of calcium on the preservation of green olives intended for black ripe olive processing under free-sodium chloride conditions. (January 2020) - García-Serrano, Pedro; Romero, Concepción; Medina, Eduardo; García-García, Pedro; de Castro, Antonio; Brenes, Manuel
Abstract: Black ripe olive processing produces large volumes of salty wastewater that may be reduced by using a salt-free solution during the preservation stage. In this study, the employment of calcium chloride and calcium lactate during this stage to improve the texture of olives of the Manzanilla, Hojiblanca and Cacereña cultivars was assessed. Neither calcium salt affected the preservation of the olives under aerobic conditions, with yeasts and acetic acid bacteria being the predominant microorganisms during this stage, whereas lactic acid bacteria were detected after several months of preservation with the increase of the ambient temperature, including Oenoccocus sp., which has not been isolated from olives until now. Moreover, both calcium salts at 20 mM concentration were equally effective in delaying the softening of olives during all processing stages regardless of the olive cultivar. In addition, the color and flavor of the olives were not affected by either of the calcium salts. Hence, these results revealed that both calcium salts must be used for the preservation stage of black ripe olives in salt-free solution without any preference for either of them from a technical point of view. Highlights: Calcium chloride and lactate did not affect fermentation of green olives. Both calcium salts delayed softening of olives. Neither calcium salt affected flavor of the olives. Oenoccocus sp. has been found for the first time in the preservation liquids of table olives. Calcium is needed for the preservation stage of black ripe olives.